Adenovirus Infection in Children With Acute Myeloid Leukemia: A Report From the Canadian Infection in Acute Myeloid Leukemia Research Group. Issue 2 (February 2018) - Renzi, Samuele; Ali, Salah; Portwine, Carol; Mitchell, David; Dix, David; Lewis, Victor; Price, Victoria; Science, Michelle; Sung, Lillian
Abstract : Background: Children with acute myeloid leukemia (AML) are at high risk of life-threatening bacterial and fungal infection. However, little is known about the prevalence or severity of adenovirus infection in this population. Objective was to describe the characteristics, treatments and outcomes of adenovirus infection in children with newly diagnosed AML. Methods: We performed a retrospective chart review based upon 2 multicenter cohort studies that focused on identifying risk factors for infection in children with AML. Inclusion criteria were patients with de novo AML who were ⩽18 years of age at diagnosis with a clinical specimen positive for adenovirus. Results: Among the 235 patients with AML, 12 (5.1%) had positive adenovirus testing. The most common site of isolation was stool (n = 11, 91.6 %), and the most frequent symptom was diarrhea (n = 11, 91.6 %). Two patients received specific treatment for adenovirus, namely intravenous immunoglobulin only in 1 patient and both intravenous immunoglobulin and inhaled ribavirin in a second patient. In 11 patients, adenovirus resolved uneventfully without recurrence, including 10 that received no adenovirus-specific therapy. However, 1 patient developed sepsis syndrome in the setting of disseminated adenoviral infection and died from multiorgan failure. Conclusion: In children with AML, adenovirus infection was rare and typically not associated with severe disease, even without specific treatment. However, disseminated and fatal disease can occur in this population. Further investigations are needed to identify pediatric AML patients at particular risk for severe adenovirus infection and to determine optimal treatment approaches in these patients.